The Cost of High Tunnel and Caterpillar Tunnel Establishment for Vegetable Production - Yefan Nian; Zhifeng Gao; Xin Zhao; Ruojin Zhao; Shufang Tian; Isaac Vincent; Zachary Ray (EDIS, 2023)
Due to increasing marketing and production risks in specialty crop production, a shift toward more protected culture systems such as a high tunnel production system is crucial to keep specialty crop farms profitable and sustainable in the United States. In this publication, we analyzed the cost of constructing high tunnels and caterpillar tunnels in Florida and examined the major contributors to their establishment costs. The findings are intended to assist farmers in deciding whether or not to add high tunnel or caterpillar tunnel systems to their farming operations.